MEMBANGUN KONSEP DIRI UNTUK MENGATASI KECEMASAN BERSEKOLAH SISWA KORBAN PERUNDUNGAN DI SEKOLAH DASAR - Dariyo, Agoes; Housen, Michael; Andrianputra, Ezra (Jurnal Serina Abdimas, 2024)
Elementary school students who experience school anxiety are triggered by past experiences due to their psychological trauma as victims of bullying from their school friends. This article aims to examine community service related to developing self-concept to overcome school anxiety among victims of bullying in elementary school students. The method for implementing PKM activities is the one-group pre-test post-test technique. The number of participants was 31 students, but after screening to obtain data on students who experienced anxiety about going to school, 11 students were obtained who were anxious about going to school. A total of 11 students were involved in developing self-concept and 20 students were not involved in developing self-concept. Data were collected by distributing school anxiety questionnaires and self-concept questionnaires. Data analysis technique using mean test calculations. The result is that the pre-test score for school anxiety is (3.545) with the post-test score for school anxiety (3.209), meaning that developing self-concept can reduce school anxiety for elementary school students. So students who are victims of bullying who participate in self-concept development are able to reduce school anxiety.